Below-knee endovascular interventions have better outcomes compared to open bypass for patients with critical limb ischemia. (February 2017) - Hicks, Caitlin W; Najafian, Alireza; Farber, Alik; Menard, Matthew T; Malas, Mahmoud B; Black, James H; Abularrage, Christopher J
Both open surgery and endovascular peripheral interventions have been shown to effectively improve outcomes in patients with peripheral artery disease, but minimal data exist comparing outcomes performed at and below the knee. The purpose of this study was to compare outcomes following infrageniculate lower extremity open bypass (LEB) versus peripheral vascular intervention (PVI) in patients with critical limb ischemia. Using data from the 2008–2014 Vascular Quality Initiative, 1-year primary patency, major amputation, and mortality were compared among all patients undergoing LEB versus PVI at or below the knee for rest pain or tissue loss. Overall, 2566 patients were included (LEB=500, PVI=2066). One-year primary patency was significantly worse following LEB (73% vs 81%; p <0.001). One-year major amputation (14% vs 12%; p =0.18) and mortality (4% vs 6%; p =0.15) were similar regardless of revascularization approach. Multivariable analysis adjusting for baseline differences between groups confirmed inferior primary patency following LEB versus PVI (HR 0.74; 95% CI, 0.60–0.90; p =0.004), but no significant differences in 1-year major amputation (HR 1.06; 95% CI, 0.80–1.40; p =0.67) or mortality (HR 0.71; 95% CI, 0.44–1.14; p =0.16). Based on these data, we conclude that endovascular revascularization is a viable treatment approach for critical limb ischemia resulting from infrageniculate arterial occlusive disease.